Indonesian Student's Difficulties in Speaking English - Dwi Melansari; Dia Fransisca; Sri Wahyuni (JEIT (Journal of Educational Innovations and Technologies), 2025)
This study examines the persistent challenges faced by Indonesian students in developing English-speaking skills. The aim of the research is to analyze the primary barriers that hinder their speaking fluency and to offer effective pedagogical recommendations. A qualitative approach was employed through a literature review by synthesizing various academic sources focused on English as a Foreign Language (EFL) learning in Indonesia. The findings reveal that students generally struggle with vocabulary acquisition, grammatical accuracy, and low self-confidence. In addition, the lack of exposure to authentic communication, teacher-centered instructional methods, and cultural norms contribute to students' reluctance to speak. Technological barriers, such as limited access to digital tools and the internet, further reduce speaking practice opportunities, particularly in rural areas. This study recommends the integration of communicative tasks into classroom routines, enhanced student engagement with authentic digital content, and the creation of a supportive learning environment where mistakes are viewed as part of the learning process. These strategies are expected to improve students' fluency, motivation, and overall ability to communicate effectively in English.